Functions of a stream unit on the growth of phytoplankton, zooplankton and fish fry in a new culture tank system - Yamasaki, S.; Hirata, H.; Cheah, S. H.; Ang, K. J.; Zainal Abidin, Aizam (Elsevier, 1988)
The functions of a stream unit in a new culture tank system, which was composed of the stream unit and a conventional tank, were evaluated by cultivation of phytoplankton (freshwater Chlorella sp.), Zooplankton (Moina micrura) and fish fry (Puntius gonionotus). Ratios of the growth rates of phytoplankton and zooplankton in the new tank system, to the control tank were 1.2:1 and 1.1:1 on average, respectively, and ratios of total weight of fish growth were 1.1:1. On the basis of the results and several water quality parameters (DO, PO4-P content and pH), the following functions were considered: (1) Enhancement of the growth of algae, water weeds, and bacteria; (a) production of food materials for zooplankton and fish, (b) oxygen supply, (c) pH increase, (d) absorption of nutrients, (e) acceleration of decompostion of biodeposits. (2) Accumulation of biodeposits.